Menedékkérők migrációs útvonalainak és tendenciáinak vizsgálata a Balkán-fészigeten = Analysis of migratory routes and tendencies of asylum seekers on the Balkan peninsula - Kovács, Áron; Farkas, Marcell; Palotai, Jenő (Közép-Európai Közlemények, 2018)
As the recent migration crisis hit the European Union, the role of analysing migration tendencies and migratory routes of asylum seekers became far more important. The Eastern Mediterranean Sea route and the Western Balkans land route provided access to the European Union for about 800 000 asylum seekers in only one year (2015–2016), mainly from Syria, Afghanistan, Iraq and Pakistan. This study deals with these recent trends from the aspect of the different land and sea migratory routes of the Western Balkans and the Eastern Mediterranean, revealing the main changes over the last few years (2009–2016). It gives us a short overview of detailed monthly border-crossing statistics as well as their background by analysing the detected number of people at the main bordercrossing points and along the borders of the countries involved. It analyses the most important trends and changes that have emerged in the Balkans. It also examines the composition of the origin of migrants. The study emphasizes Hungary’s role in changing migration trends.